TRENDS AND CHALLENGES FOR THE PERUVIAN UNIVERSITIES' LIBRARIES IN THE MANAGEMENT OF ACADEMIC KNOWLEDGE - Morgan Rozas, Milagros Angélica (2007)
In the administration of academic knowledge, the trends towards which the Peruvian universities’ libraries are steering their ship to are identified. Starting from these, a reflection is made about the reason of being of each one of them and challenges are put forth that allow the libraries to evidence their contribution to the betterment of the teaching and learning processes, as well as the generation and diffusion of scientific knowledge. It begins from the hypothesis that establishes that Peruvian universities’ libraries are walking towards a Center of Resources for Learning and Investigation (CRLI) model, without stopping to offer the traditional services that they are normally assigned. To investigate this issue, the revision of Internet web pages is used as a resource, as well as the information published at QUELCAS, the web page for the Peruvian Libraries which corresponds to a sample of 32 academic Peruvian libraries (56% of which are members of ALTAMIRA, 36% are located outside the city of Lima and 19% are state universities). The results evidence diverse trends in the roles of the libraries in the administration of academic knowledge, demonstrate the impact of the actions taken by ALTAMIRA and point to the various lines of work and investigation that will contribute to develop libraries that will respond in a proactive manner to the new models of teaching and learning, as well as networking.